Enhancement of the electrochemical performance of lithium-ion batteries by SiO2@poly(2-acrylamido-2-methylpropanesulfonic acid) nanosphere addition into a polypropylene membrane. Issue 9 (30th January 2020) - Yang, Guoping; Cai, Haopeng; Li, Xiangyu; Wu, Mengjun; Yin, Xue; Zhang, Haining; Tang, Haolin
Abstract : The surface of SiO2 nanospheres was coated with poly(2-acrylamido-2-methylpropanesulfonic acid) bearing strong electron withdrawing sulfonic and amide groups, enhancing the dissociation ability of the lithium salt of the liquid electrolyte and absorbing anions via H-bonds. Abstract : Employing electrostatic self-assembly and free radical polymerization, the surface of SiO2 nanospheres was coated with poly(2-acrylamido-2-methylpropanesulfonic acid) (SiO2 @PAMPS) bearing strong electron withdrawing sulfonic and amide groups, enhancing the dissociation ability of the lithium salt of the liquid electrolyte and absorbing anions via hydrogen bonds. After SiO2 @PAMPS nanospheres were introduced into the polypropylene (PP) membrane (SiO2 @PAMPS/PP), the electrolyte affinity and electrolyte uptake of the composite separators were significantly improved. The ionic conductivity of SiO2 @PAMPS/PP-18% (where 18% represents the concentration of the solution used for coating) soaked in liquid electrolyte was even 0.728 mS cm −1 at 30 °C, much higher than that of the pristine PP membrane. The LiFePO4 /Li half-cell with SiO2 @PAMPS/PP-18% had a discharge capacity of 148.10 mA h g −1 and retained 98.67% of the original capacity even after 120 cycles at 0.5C. Even at a rate of 1.0C, the cell capacity could be maintained above 120 mA h g −1 . Therefore, a coating formula was developed that could considerably improve the cycling ability and high rate charge–discharge performance of lithium ion batteries.